2021
DOI: 10.3389/feart.2021.758606
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Vertical Point Accuracy: Assessing Inter-pixel Consistency in 30 m Global DEMs for the Arid Central Andes

Abstract: Quantitative geomorphic research depends on accurate topographic data often collected via remote sensing. Lidar, and photogrammetric methods like structure-from-motion, provide the highest quality data for generating digital elevation models (DEMs). Unfortunately, these data are restricted to relatively small areas, and may be expensive or time-consuming to collect. Global and near-global DEMs with 1 arcsec (∼30 m) ground sampling from spaceborne radar and optical sensors offer an alternative gridded, continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 94 publications
(200 reference statements)
0
14
1
1
Order By: Relevance
“…Alguns trabalhos têm se preocupado em avaliar as formas de relevo, derivações geomorfométricas (e.g. declividade e orientação de vertentes), rede de drenagem e consistência inter-pixel obtidas pelo MDE e não apenas a acurácia vertical do dado (POLIDORI; EL HAGE; VALERIANO, 2014; TOLENTINO, SILVA, SANTIL, 2017; MOZAS-CALVACHE, UREÑA-CÁMARA; ARIZA-LÓPEZ, 2017;ALBA-FERNÁNDEZ, 2021;PURINTON;BOOKHAGEN (2021). Nesse sentido, estudos complementares podem ser explorados para avaliar a qualidade das derivações possíveis de se extrair com o COP-30.…”
Section: Resultados E Discussõesunclassified
“…Alguns trabalhos têm se preocupado em avaliar as formas de relevo, derivações geomorfométricas (e.g. declividade e orientação de vertentes), rede de drenagem e consistência inter-pixel obtidas pelo MDE e não apenas a acurácia vertical do dado (POLIDORI; EL HAGE; VALERIANO, 2014; TOLENTINO, SILVA, SANTIL, 2017; MOZAS-CALVACHE, UREÑA-CÁMARA; ARIZA-LÓPEZ, 2017;ALBA-FERNÁNDEZ, 2021;PURINTON;BOOKHAGEN (2021). Nesse sentido, estudos complementares podem ser explorados para avaliar a qualidade das derivações possíveis de se extrair com o COP-30.…”
Section: Resultados E Discussõesunclassified
“…In contrast, some studies such as Gesch (2018) and Hawker et al (2022), focused their analysis primarily on coastal or floodplain terrain which probably accounts for our finding that FABDEM often ranked lower than the COPDEM from which it was derived. At the other elevation extreme in mountain areas, Purinton and Bookhagen (2021) preferred COPDEM while Florinsky et al (2019) and Trevisani et al (2022) found that relative performances between COP and ALOS change according to local morphology, with ALOS slightly better in steep slopes. None of those works provide a confidence level for their conclusions.…”
Section: Comparing the Demix Wine Contest Methods And Rankings To Pre...mentioning
confidence: 97%
“…Created reference DEMs to consider the half pixel offset between ALOS and COPDEM (and the other lower quality DEMs) for the inter-comparison, a consequence of the decision not to resample candidate DEMs. This issue is generally not discussed in the literature (or addressed by interpolation) although Purinton and Bookhagen (2021) designed their comparisons to avoid the need for DEM co-registration.…”
Section: Comparing the Demix Wine Contest Methods And Rankings To Pre...mentioning
confidence: 99%
“…The global RMSE of COP30 DEM is ±1.68 m (AIRBUS, 2020). Several studies have pointed out that this DEM is the most reliable open-access DEM to date (Purinton and Bookhagen, 2021;Guth and Geoffroy, 2021). The source images of COP30 DEM were mostly acquired between 2011 and 2014, and therefore COP30 DEM is suitable to represent the surface elevation in the 2010s.…”
Section: Elevation Datamentioning
confidence: 99%